A Study on the Experience of the Visually Impaired In an Effort to Minimize Stereotypic Behaviour through Self-Management: Barriers and Support - Mohammad Anwar; Donni Prakosha; Tias Martika (Journal of ICSAR, 2022)
This study aims to explore aspects that support and hinder the development process of self-management skills for visually impaired children in order to minimize stereotypic behavior that can interfere with the learning process in special schools. There are 30 visually impaired children as the subjects of the research. Data were collected through surveys, semi-structured interviews and they were analyzed by using content analysis methods. The results showed that the cause/inhibitory aspect included a slight stimulus that could be caused by a lack of socialization and social isolation so that the visually impaired seek additional stimuli through repetition of behavior, limited physical activity, and inadequate support/assistance from parents/teachers. While aspects that support the development of self-management for the visually impaired in minimizing stereotypic behavior are the support of school and college facilities, support from peers, and increased awareness of teachers, parents and academics on the important role of self-management for them.